Ensaios bioanalíticos em dispositivos fabricados em poliéster-toner - Oliveira, Karoliny Almeida (2013)
This report describes the fabrication of polyester-toner (PT) devices to perform bioanalytical assays. The direct-printing technology has been explored to produce (i) printed microplates containing 96 zones and (ii) integrated microfluidic devices. Overall, the device layouts were designed on the Corel Draw® software and printed on a polyester film surface by using a laser printer. Toner-based 96-zones were created by the deposition of toner barriers with thickness of ca. 5 μm. All zones were distributed into 12 columns and 8 lines. During the analytical performance investigation with a conventional microplate reader, it was observed that the zone diameter and the sample volume added on each zone directly affect the absorbance response. After the optimization step, printed microplates were used to demonstrate the bioanalytical feasibility with enzyme-linked immunosorbent assay (ELISA) coupled with a microplate reader or a cell phone camera. Immunoglobulins G (IgG) and M (IgM) antibodies were successfully detected in cell culture cell and human serum samples, respectively. The limit of detection achieved for IgG was 0.2 g/mL (13 fmol/zone). The IgM detection was used to evaluate the printed microplates feasibility for dengue diagnostics. The assays performed with both microplate reader and cell phone camera allowed distinguishing samples from infected and noninfected patients. Furthermore, it was found that the lifetime of each printed microplate depends on the storage temperature. The half life for devices stored at 10 °C has been estimated to be ca. four weeks. In addition to printed microplates, this current report also covers the fabrication of microfluidic devices containing detection zones interconnected by microchannels. These devices were produced with three polyester films. The intermediary layer was previously cut and added on the device to increase the channel depth and to provide the solution transport by capillary action. The three polyester layers were laminated together to obtain a microchannel with ca. 110 μm deep. The device proposed in this report was tested to monitor the enzymatic reaction kinetics for glucose in the presence of glucose oxidase (GOX), peroxidase and potassium iodide. The colorimetric response was recorded with a scanner. The Michaelis-Menten constant achieved with this analytical tool for the mentioned enzymatic reaction was 8.8 mM. This value is similar to the data reported in literature. These devices were also explored to quantitatively determine the glucose concentration in artificial serum samples. The analytical concentrations found in serum samples levels I and II were 4.3 ± 0.5 and 14.3 ± 1.2 mM, respectively and the error found was lower than 8%. The recovery factor found in four concentration levels (five independent measurements) was higher than 95%.